2006
DOI: 10.2307/40264550
|View full text |Cite
|
Sign up to set email alerts
|

On Race, Language, Power and Identity: Understanding the Intricacies through Multicultural Communication, Language Policies, and the Ebonics Debate

Abstract: Intercultural Communication: An Advanced Resource Book. A. Holliday, M. Hyde, and J. Kullman Language Policy: Theory and Method. T. Ricento Ebonics: The Urban Education Debate (2nd Edition). J. Ramirez, T. Wiley, G. de Klerk, E. Lee, and W. Wright

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…In the United States, race and language are intricately connected, with scholars describing the practice of linguicism (i.e., discrimination based on primary spoken (non-English) language) and expressing that “language is a social practice that shapes subjectivity and establishes power relations among members of different racial and class groups” [ 5 ]. English language proficiency, which may be correlated with race/ethnicity [ 6 , 7 ], is however less frequently considered in the study of health disparities among children.…”
Section: Introductionmentioning
confidence: 99%
“…In the United States, race and language are intricately connected, with scholars describing the practice of linguicism (i.e., discrimination based on primary spoken (non-English) language) and expressing that “language is a social practice that shapes subjectivity and establishes power relations among members of different racial and class groups” [ 5 ]. English language proficiency, which may be correlated with race/ethnicity [ 6 , 7 ], is however less frequently considered in the study of health disparities among children.…”
Section: Introductionmentioning
confidence: 99%
“…However, as previously demonstrated, when the heterogenous linguistic practices of these Black and Brown girls were compared to or measured against Whiteness , they were raciolinguistically positioned as invisible or a deficit within the figured worlds of their science learning spaces. For example, Teresa's experiences, when occupying the figured world of science, demonstrated that when she moved to the U.S. and her linguistic practices were perceived by the “listening subject” and measured against Whiteness , she experienced language‐based racial profiling, or linguicism (Parmegiani, 2006), as she described:
The problem here [in the U.S.] is that like we do have accents because we don't practice. Like you're not like, "oh my god , Vanessa , hi" *expressed without placing an emphasis on her accent* It's just Spanish all the time, you know?
…”
Section: Resultsmentioning
confidence: 99%
“…Mastery of this language is a precondition for claiming symbolic and material resources. One could even argue that, while overt racism is becoming less acceptable in democratic societies, linguicism, or discrimination based on language (Phillipson 1991), continues to reign undisturbed as an alleged "politically correct" mechanism for re(producing) social stratification (Parmegiani 2006a).…”
Section: Introductionmentioning
confidence: 99%